2018
DOI: 10.1016/j.supflu.2018.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical carbon dioxide foaming of polycaprolactone for bone tissue regeneration

Abstract: Highlights- A physiologically friendly polycaprolactone foaming procedure  Use of dense CO2 as foaming agent for creation of porous three-dimensional structures of polycaprolactone without supercritical conditions  A one step approach for foaming and loading of polycaprolactone with bioactive agents such as ß-tricalcium phosphate and dexamethasone

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…In a study by Duarte et al, Obtained scaffolds of PCL, β-TCP and dexamethasone using CO 2 as a foaming agent, obtaining supernatants for only 24 hours for MTT testing. They found that there is a decrease in cell viability from ~130% for PCL to ~122% for PCL/β-TCP and ~99% for PCL/β-TCP/5% dexamethasone, concluding that, although cell viability changes, surfaces do not affect the metabolic activity of L929 osteoblast cells 49 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Duarte et al, Obtained scaffolds of PCL, β-TCP and dexamethasone using CO 2 as a foaming agent, obtaining supernatants for only 24 hours for MTT testing. They found that there is a decrease in cell viability from ~130% for PCL to ~122% for PCL/β-TCP and ~99% for PCL/β-TCP/5% dexamethasone, concluding that, although cell viability changes, surfaces do not affect the metabolic activity of L929 osteoblast cells 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Typical functionalization of PCL for bone applications include reinforcement with a mineral component such as β‐TCP (Abbah, Lam, Hutmacher, Goh, & Wong, 2009; Abbah, Lam, Ramruttun, Goh, & Wong, 2011b), or CaP with or without further addition with BMP‐2 (Abbah, Lam, Ramruttun, Goh, & Wong, 2011a; Yong et al, 2014), yet herein, the combination of pDA and pMAA provided the adhesive properties to PCL, while simultaneously inducing mineralization of the structure (Figure 6). In a previous work, the authors have successfully incorporated dexamethasone and TCP via carbon dioxide foaming of PCL, which could be added to the formulation to further improve osteogenesis (R. M. Duarte et al, 2018). This ability to induce the formation of a bone‐like HA layer has been reported to be a factor that strongly enhances the integration of the scaffold with the bone tissue and therefore pivotal for a successful healing and tissue regeneration (El‐Ghannam & Ducheyne, 2011; Hill, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In previous work (R. M. Duarte, Correia‐Pinto, Reis, & Duarte, 2018), the authors reported successful carbon dioxide foaming of PCL in subcritical, physiologically friendly conditions (5.0 MPa and 45°C), while incorporating bioactive agents such as dexamethasone and β‐tricalcium phosphate (TCP), to aid osteogenesis. The use of CO 2 as a porogen agent has significant advantages over others, namely, the fact that this is a physical foaming agent.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the environmentally friendly packaging material designed especially for drugs and food is one of the most significant commercial applications of PCL. However, the commercially available PCL with a linear chain structure has insufficient heat resistance, low melt strength, and deficient thermomechanical strength, greatly restricting its processability such as thermoforming, foaming as well as blow molding . For that reason, many research studies have been performed on the modification of its physicochemical structure and properties by blending, copolymerization and grafting …”
Section: Introductionmentioning
confidence: 99%